PENGARUH TEKANAN WAKTU, LOCUS OF CONTROL, TINDAKAN SUPERVISI DAN MATERIALITAS TERHADAP PENGHENTIAN PREMATUR ATAS PROSEDUR AUDIT - Rangga Purnama; Moh. Amin; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2019)
ABSTRACTThis study aims to determine the Influence Time Pressure, Locus of Control, Supervision and Materiality of Premature Termination of Audit Procedures. This research includes descriptive research with a quantitative approach. The population in this study is a Public Accountant in the city of Malang. With a sample of 60 Public Accountants in Malang. The sampling technique is purposive sampling. The data collection technique used was a questionnaire.The results of this study indicate that Simultaneously proves that independent or independent variables simultaneously or jointly influence the dependent variable or bound. That is, time pressure, locus of control, supervision and materiality measures have a significant effect on premature termination of audit procedures. Variables of Locus of Control and Maternity have a significant effect on premature on audit procedures. This is indicated by a significant value of 0,000 <0,05. This means that the higher the Materiality and Locus Of Control, the higher the rate of premature termination of the audit procedure. Variables of Locus Of Control have a significant effect on premature termination of audit procedures. This is indicated by a significant value of 0.009 <0.05. This means that the higher Locus Of Control, the higher the rate of premature termination of the audit procedure. Maternity variables have a significant effect on premature termination of audit procedures. This is indicated by a significant value of 0.044 <0.05. This means that the higher the Materiality, the higher the rate of premature termination of the audit procedure. Keywords: Effect Of Time Pressure, Locus Of Control, Supervision Action And Materiality.